2022
DOI: 10.3390/ijms232113015
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin-V Improve Mitochondrial Respiration and Cardiac Function in a Rat Model of Diabetic Cardiomyopathy via Inhibiting Pyroptosis Pathway through P2X7 Receptors

Abstract: There is a new form of puerarin, puerarin-V, that has recently been developed, and it is unclear whether puerarin-V has a cardioprotective effect on diabetic cardiomyopathy (DCM). Here, we determined whether puerarin-V had any beneficial influence on the pathophysiology of DCM and explored its possible mechanisms. By injecting 30 mg/kg of STZ intraperitoneally, diabetes was induced in rats. After a week of stability, the rats were injected subcutaneously with ISO (5 mg/kg). We randomly assigned the rats to eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Contrary to this study, Cai et al (1989) stated that myocardia layer was thinner in diabetic male rat heart (28). Cai et al (1989) and Sun et al (1993) expressed that there was damage to myofibrils in the heart muscle cell (28,29). Çetin et al (2013) mentioned that pycnotic nuclei and eosinophilic cytoplasm were observed in myocyte of heart in the experimental diabetic group (30).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this study, Cai et al (1989) stated that myocardia layer was thinner in diabetic male rat heart (28). Cai et al (1989) and Sun et al (1993) expressed that there was damage to myofibrils in the heart muscle cell (28,29). Çetin et al (2013) mentioned that pycnotic nuclei and eosinophilic cytoplasm were observed in myocyte of heart in the experimental diabetic group (30).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the dose of 25 µL/mL of DHI exhibited more significant suppression of cell pyroptosis compared to a normal dosage of NSA [118]. Puerarin V is a newly identified form of puerarin that has been shown to ameliorate myocardial injury in DCM rats by regulating NLRP3/caspase-1/GSDMD-dependent pyroptosis, and it was further reported that puerarin-V exhibits a greater effect than puerarin, puerarin injections, or metformin in DCM [125]. Gypenosides, which are the main components of Gynostemma pentaphyllum, can inhibit ROS-induced activation of the NLRP3 inflammasome caused by cytochrome c, improve myocardial cell injury in H9c2 cells, and inhibit the development of DCM in vivo [126].…”
Section: Herbal Medicine and Monomersmentioning
confidence: 98%
“…A new crystal form of puerarin, puerarin‐V, has been developed. Sun et al (2022) reported that puerarin‐V could regulate lipid metabolism in DCM rats, inhibit myocardial inflammation and fibrosis, improve antioxidant levels, and enhance cardiac function and mitochondrial respiratory function. Its possible mechanism involves inhibiting the expression of the P2X7 receptor, blocking the NLRP3‐Caspase‐1‐GSDMD pathway, thereby reducing pyroptosis and myocardial injury.…”
Section: Natural Substances Treat Dcm By Targeting Different Pcdsmentioning
confidence: 99%